2020
DOI: 10.1109/access.2020.3022213
|View full text |Cite
|
Sign up to set email alerts
|

Remote Thermal Water Leakage Sensor With a Laser Communication System

Abstract: The change in the temperature of an underground water pipeline and its surrounding environment caused by a leakage has been detected by a variety of devices. Among the most popular technologies are infrared cameras, distributed temperature sensing using fiber optic cables, and analog active temperature sensors. In this paper, a novel low-cost leakage detection system composed of two analog active temperature sensors is presented. The proposed system detects water leakages by comparing the readings of two analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…They deduced that both wave speed and attenuation are higher for a buried pipe. Awwad et al (2020) used a remote setup using temperature sensors for detecting leaks. The study observed temperature differences in the soil every 17 min to make predictions.…”
Section: Design Parameters Of Leak Experimentsmentioning
confidence: 99%
“…They deduced that both wave speed and attenuation are higher for a buried pipe. Awwad et al (2020) used a remote setup using temperature sensors for detecting leaks. The study observed temperature differences in the soil every 17 min to make predictions.…”
Section: Design Parameters Of Leak Experimentsmentioning
confidence: 99%
“…Although the efficiency of an IR camera has been determined using the optimum time to use the camera [37], the distance of the camera from the source [37,38], and the rate of capturing images [37], previous studies ignored the efficiency of IR cameras in wide-ranging pipe materials and soils, as well as environmental characteristics (such as different levels of MC). Apart from the IR camera, the thermal leak detection approach was also successful [39]. The IR camera successfully detected the leaks as a thermal contrast at the pavement surface that occurred in fall and spring seasons, while it failed in detecting leaks occurring in the summer and winter due to high pavement temperature and the snow coverage, respectively.…”
Section: Infrared (Ir) Cameramentioning
confidence: 99%
“…The authors of [13] also developed a WSN with thermal sensors to detect water leaks in pipes. In this case, the system detects temperature changes of the soil above the leakage, allowing the user to be warned of a possible leak location.…”
Section: Related Workmentioning
confidence: 99%
“…To improve the efficiency of water distribution and to reduce waste related to leaks, a sensor network can be used to execute those analyses with precision and in an autonomous way. Some research and development can be found in both the academic and industrial worlds, ranging from expansive fixed systems that use ultrasonic clamps to analyze real-time water flow, such as [11], to low-cost solutions found in the academic world, such as [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%